Impact of the Nature of Energy Management and Responses to Policies Regarding Solar and Wind Pricing: A Qualitative Study of the Australian Electricity Markets - Alsaedi, Yasir; Tularam, Gurudeo Anand; Wong, Victor (International Journal of Energy Economics and Policy, 2021)
The present study employed various qualitative techniques to investigate the nature and influence of policies and regulations concerning solar and wind pricing on the Australian electricity spot and options markets. The analysis was based on data gathered through interviews conducted with energy managers, chief executive officers and other significant personnel from the Australian electricity industry. The interviewees’ responses regarding the solar and wind policies of relevance to the Australian electricity markets were examined, and the thick and in-depth content data derived from the interviews were used to examine how their views and personal politics influenced pricing within the electricity markets. The results suggest that renewable energy policies lower the electricity prices, reduce the risks for investors and also result in larger deployment mechanisms. Keywords: Electricity pricing, Renewable energy, Energy policies. JEL Classifications: Q13, Q4, Q42 DOI: https://doi.org/10.32479/ijeep.10991